Sarau Palavra Encantada no Cantinho Girassol: um espaço cultural na periferia da cidade de Sorocaba - Oliveira, Marco Aurélio Nunes de (Universidade Federal de São Carlos, 2018)
This work had as purpose the analysis of a cultural experiment in the suburb of Sorocaba city. Approach the potentiality of the Sarau Palavra Encantada that happens at the pub Cantinho Girassol as a meeting space, in the regards of the pub as a meeting place, local for exchange of cultural know-how and for the right to the city. Its about a case study. To this, developed a reference list about the concerning research thematic, particularly about: (I) Sorocaba city, (II) its suburbs and (III) occupation of its urban places. Performed semi-structured interviews with recurrent visitors of the cultural place, also consulted regional newspapers archives, in which the meeting place is shown. The objectives included the understanding of the relation amongst the place Cantinho Girassol and the community, in the context of Sorocaba city metropolitan area growth, stigmatized by segregation and privatize of the cultural place, where leisure is related to consumption, as well as the potential of the Sarau Palavra Encantada as a cultural place in Sorocaba city.
Keywords: Direito à Cidade; Espaços Culturais; Periferias; Sarau; Right to the city; Cultural places; Suburbs; Literary meeting; CIENCIAS HUMANAS::EDUCACAO